Elevated Blood S100B Levels in Patients With Migraine: A Systematic Review and Meta-Analysis - Chu, Chaojia; Zhong, Rui; Cai, Mengtan; Li, Nan; Lin, Weihong (Frontiers in Neurology, 2022)
Background: In recent years, a growing number of researches indicate that S100B may act in migraine, but the relationship between S100B and migraine remains controversial. Therefore, the current study aimed to perform a meta-analysis to quantitatively summarize S100B levels in migraine patients. Methods We used Stata 12.0 software to summarize eligible studies from PubMed, EMBASE, Web of Science, Cochrane Library, China National Knowledge Infrastructure (CNKI), and Wanfang databases. We applied standardized mean differences (SMDs) with 95% confidence intervals (95%CIs) to appraise the association between S100B and migraine. Results The combined results of nine case-control studies indicated that compared with healthy controls, overall migraine patients had significantly increased S100B levels in peripheral blood (SMD = 0.688, 95%CI: 0.341–1.036, P < 0.001). The S100B levels in migraineurs during ictal periods (SMD =1.123, 95%CI: 0.409–1.836, P = 0.002) and interictal periods (SMD = 0.487, 95%CI: 0313–0.661, P < 0.001), aura (SMD = 0.999, 95%CI: 0.598–1.400, P < 0.001) and without aura (SMD = 0.534, 95%CI: 0.286–0.783, P < 0.001) were significantly higher than those in the controls. The subgroup analyses by age, country, migraine assessment, and assay method of S100B also illustrated a statistically obvious association between S100B levels and migraine, indicating that age may be the most important source of heterogeneity. Sensitivity analysis showed that no individual study has a significant influence on the overall association between S100B and migraine. Conclusion This meta-analysis demonstrates that the level of S100B in peripheral blood of patients with migraine was significantly increased. Migraine may be associated with pathological reactions involving S100B, which is instrumental for the clinical diagnosis of migraine and therapy that considers S100B as a potential target.